The Cell Biology and Role of Resorptive Cells in Diseases: A Review - Babaji, Prashant (Ann Afr Med, 2017)
Resorptive cells are responsible for the resorption of mineralized matrix of hard tissues. Bone-resorbing cells are called osteoclasts; however, they can resorb mineralized dental tissues or calcified cartilage and then they are called odontoclasts and chondroclasts, respectively. Resorptive cells form when mononuclear precursors derived from a monocyte–macrophage cell lineage are attracted to certain mineralized surfaces and subsequently fuse and adhere onto them for exerting their resorbing activity. These cells are responsible for degradation of calcified extracellular matrix composed of organic molecules and hydroxyapatite. The activity of these cells can be observed in both physiological and pathological processes throughout life and their activity is mainly required in bone turnover and growth, spontaneous and induced (orthodontic) tooth movement, tooth eruption, and bone fracture healing, as well as in pathological conditions such as osteoporosis, osteoarthritis, and bone metastasis. In addition, they are responsible for daily control of calcium homeostasis. Clastic cells also resorb the primary teeth for shedding before the permanent teeth erupt into the oral cavity.